1997
DOI: 10.1117/1.601402
|View full text |Cite
|
Sign up to set email alerts
|

Application of two-dimensional wavelet transform to hologram analysis: visualization of glass fibers in a turbulent flame

Abstract: In different fiberization processes, glass fibers are drawn out in a turbulent flame. High-speed in-line holography is applied to visualize glass fibers. However, the random spatial distribution of temperature induces strong local variations of the refraction index. Consequently, the reconstructed images are altered. The direct analysis of the diffraction patterns recorded by the holographic plate can offer an alternative solution. The diffraction process can be interpreted as a convolution with a wavelet fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…9 In our laboratory, R(x,y) is either computed by applying a wavelet transformation or a Fractional Fourier Transformation. 2,7,10 It is easy to show that when z r =z e =z, and by introducing (4) in (5), we obtain :…”
Section: Hologram Reconstructionmentioning
confidence: 98%
“…9 In our laboratory, R(x,y) is either computed by applying a wavelet transformation or a Fractional Fourier Transformation. 2,7,10 It is easy to show that when z r =z e =z, and by introducing (4) in (5), we obtain :…”
Section: Hologram Reconstructionmentioning
confidence: 98%
“…Here, note that the intermodulation term has been dropped. In fact, it is shown that when large recording distances are considered such that z 0 >>πd 2 /λ where d is the object diameter, this term can be treated as a constant and can be neglected [5]. The expression given by Eq.…”
Section: Digital Reconstruction Of In-line Hologramsmentioning
confidence: 99%
“…With the recent development of CCD cameras, it is now possible to record holograms in real-time. For a few years, it has been known that the 3-D location of particles or fibers can be accurately determined by numerical reconstruction of holograms that are directly recorded by a camera [5,6]. Recently, it has been shown that the reconstruction process can be seen either as a wavelet transformation or as a Fractional Fourier transformation of the intensity distribution recorded by the hologram [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The practical implementation of digital holography was advanced in the 1990s. In order to realize numerical reconstruction of in-line holography, different algorithms have been developed based on Fresnel integral [1,2], discrete Fourier transform [3][4][5] and wavelet transform [6,7], respectively. The algorithm based on wavelet transform has advantages such as high resolution and high signalto-noise ratio of reconstructed images.…”
Section: Introductionmentioning
confidence: 99%